Reconstruction of the lower eye lid with a rotation-advancement tarso-conjunctival cheek flap - Wessels, William Louis Fick (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MMed (Surgical Sciences. Plastic and Reconstructive Surgery))--University of Stellenbosch, 2010.